Analysis of factors of students’ stress of the English Language Department - Siwi Karmadi Kurniasih; Nur Hidayanto Pancoro Setyo Putro; Sudiyono Sudiyono (Program Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2020)
The study is aimed at further describing psychological factors inducing academic stresses of the students of the English Education Department, Yogyakarta State University (EED-YSU). The study is a continuation of a previous study that identifies sources of academic stress of students of EED-YSU. Data collection is conducted by an on-line survey technique. Confirmatory factor analysis is used for the data analyses. The results show six factors that become sources of students’ academic stresses, namely academic demands, parent-child relationship, traumatic experiences during childhood, peer pressures, financial matters, and self-expectancy. It is expected that other studies involving other factors of students’ academic stress be conducted to give further information on the topic.